Implementation of Sharia Compliance in ZIS Distribution at BSI Maslahat Based on DSN-MUI Fatwas - Salsabilla, Salma Nadia; Setiyowati, Arin; Latifah, Luluk (UIN Siber Syekh Nurjati Cirebon, 2025)
The implementation of Sharia compliance in the management of zakat, infaq, and sadaqah (ZIS) funds is essential to ensure public trust and institutional accountability. This study aims to examine the extent to which BSI Maslahat, the official amil zakat institution affiliated with Bank Syariah Indonesia (BSI), complies with Sharia principles in distributing ZIS funds, particularly in terms of transparency and accountability. This research uses a qualitative method with a literature and documentary study approach. The data were sourced from BSI Maslahat’s annual reports from 2017 to 2023 and relevant fatwas issued by the National Sharia Council–Indonesian Ulema Council (DSN-MUI). Content analysis was applied to assess the alignment of ZIS distribution with Sharia principles, particularly DSN-MUI Fatwa No. 23/2020 and No. 71/2023. The findings indicate that ZIS distribution during the observed period did not fully comply with Fatwa No. 23/2020, as the riqab category was not included. However, improvements in transparency and reporting were evident in accordance with Fatwa No. 71/2023. These results are analyzed through Monzer Kahf’s Islamic Contract Theory, which emphasizes justice, transparency, and Sharia adherence. This study contributes to Islamic economic discourse by offering strategic recommendations to enhance ZIS fund management and compliance. It also serves as a reference for regulators and Islamic financial practitioners to improve institutional governance and public confidence in Islamic philanthropy.Keywords: BSI Maslahat; Sharia Compliance; ZIS Distribution; DSN-MUI; Islamic Contract Theory